ISLAMIC MULTICULTURALISM In the Implementation of the Independent Curriculum in SMA - Mufidul Abror; An’im Fattach (Sean Institute, 2022)
The government's policy in post-pandemic education is a new breakthrough which is expected to be able to prepare a generation that is noble, creative, innovative and globally diverse, namely by implementing an independent curriculum. This study uses a library research method with a descriptive analysis approach. The data in this study include primary and secondary data by finding sources which are then analyzed. There are at least two aspects of Islamic multiculturalism in the Implementation of the Independence Curriculum in SMA, namely the content of Islamic Religious Education subject matter and the dimensions of the Pancasila student profile.